Analysis of Fragrance Allergens in Personal Care Products, Toys, and Water Samples: A Review. (24th December 2021) - Chen, Jing; Yi, Zonghui; Sun, Rui; Ning, Wei; Zhou, Chen; Tian, Ziyi; Sun, Chengjun; Li, Yongxin
Abstract: Fragrance allergens (FAs) refer to these volatile or semi-volatile fragrance compounds that can cause irritation and negative reactions. A large number of emerging FAs are widely used in household goods, and cause contact allergy or allergic contact dermatitis in eczema population and the general population. It shows an increasing prevalence and is regarded as a concern to public health. Recently, more and more studies have focused on the analytical methods of FAs in a variety of samples with different matrixes. Therefore, a systematic and comprehensive overview of recent progress of analysis of FAs in various samples is needed. In this review, the physical and chemical properties, applications, hazards, and the recent advances of sample preparation and determination methods of common FAs in personal care products, toys, and water samples are systematically and comprehensively summarized. Meanwhile, this review also discusses the advantages and limitations of different sample pretreatment and detection methods, thus offering a deep-going discussion of the development and future trends in this area